DePoLean (Detergent Pollutant Cleaner) Detergent Pollutant Cleaner Based On Soybean Fermentation - Zulfa Firdausi Husna; Siti Yanuar Arofah; Nurfi Misyka; Fayyaza Amalia Islami; Ilma Khoirunissa (SMA Trensains Muhammadiyah Sragen, 2022)
The increasing population in Indonesia is proportional to the increase in the use of detergents. Detergent is an active pollutant that causes an increase in water pollution. One of the efforts to reduce the levels of detergent pollutants is to use soybeans fermented by the bacterium Bacillus subtilis. Fermented soybeans contain polyglutamic acid which is a natural water purifier. The utilization of soybeans in this study is because soybeans are easy to find in Indonesia, safe terms of health, and have an economical price. The research conducted at SMA Trensains Muhammadiyah Sragen aims to reduce the levels of detergent pollutants in water by filtrated them. This study uses the grounded theory method, namely research that starts from an existing theory. Then field observations were made to test the truth of the previous theory. The results showed that soybean fermentation was proven to be able to reduce the levels of detergent pollutants in the water so that the water can be uses.